BindingDB Entry 50047890: Screening and Design of Inhibitor Scaffolds for the Antibiotic Resistance Oxacillinase-48 (OXA-48) through Surface Plasmon Resonance Screening. - BindingDB (BindingDB, 2018)
Small molecule binding data for protein Beta-lactamase